A new Miocene baleen whale from Peru deciphers the dawn of cetotheriids. Issue 9 (13th September 2017) - Marx, Felix G.; Lambert, Olivier; de Muizon, Christian
Abstract : Cetotheriidae are an iconic, nearly extinct family of baleen whales (Mysticeti) with a highly distinct cranial morphology. Their origins remain a mystery, with even the most archaic species showing a variety of characteristic features. Here, we describe a new species of archaic cetotheriid, Tiucetus rosae, from the Miocene of Peru. The new material represents the first mysticete from the poorly explored lowest portion of the highly fossiliferous Pisco Formation (allomember P0), and appears to form part of a more archaic assemblage than observed at the well-known localities of Cerro Colorado, Cerro los Quesos, Sud-Sacaco and Aguada de Lomas. Tiucetus resembles basal plicogulans (crown Mysticeti excluding right whales), such as Diorocetus and Parietobalaena, but shares with cetotheriids a distinct morphology of the auditory region, including the presence of an enlarged paroccipital concavity. The distinctive morphology of Tiucetus firmly places Cetotheriidae in the context of the poorly understood 'cetotheres' sensu lato, and helps to resolve basal relationships within crown Mysticeti.